Association fiber tracts related to Broca’s area: A comparative study based on diffusion spectrum imaging and fiber dissection - Wu, Yupeng; Liu, Jihui; Yu, Guoning; Jv, Ronghui; Wang, Yibao; Zang, Peizhuo (Frontiers in Neuroscience, 2022)
Broca’s area, made up of Brodmann areas (BA) 44 and 45 in the ventrolateral frontal region, is associated with language production and articulation. A comprehensive network analysis of Broca’s area is necessary for understanding language function, which is still lacking. In this study, we attempted to investigate the association fiber tracts related to Broca’s area using both diffusion spectrum imaging (DSI) and postmortem fiber dissection. DSI was performed on 10 healthy subjects and an atlas comprising the average data of 842 healthy subjects from the Human Connectome Project. Fiber dissection was implemented in 10 cerebral hemispheres of cadaver donors. The following five association fiber tracts related to Broca’s area were identified: first, the distinct fasciculus of the inferior fronto-occipital fasciculus (IFOF), from Broca’s area (BA44, BA45) and pars orbitalis (BA47) to the parietal and occipital lobes; second, the ventral superior longitudinal fasciculus (SLF-III), from the supramarginal gyrus (BA40) to the ventral precentral gyrus (PreG, BA6) and posterior Broca’s area (BA44); third, the arcuate fascicle (AF), from the superior, middle, and inferior temporal gyrus (BA20, BA21, BA22) to Broca’s area (BA44, BA45) and ventral PreG; fourth, the frontal aslant tract (FAT), from Broca’s area (BA44, BA45) to the lateral superior frontal gyrus (SFG), medial SFG, and supplementary motor area (BA6, BA8, BA9); and fifth, the frontal longitudinal fasciculus (FLF), a novel intralobar frontal association fiber tract, from the anterior part of the middle frontal gyrus (MFG, BA46) and Broca’s area (BA45) to the caudal MFG (BA8), caudal SFG, and dorsal PreG (BA6). Moreover, compared with the left FAT, the right FAT covered almost the entire inferior frontal gyrus (BA44, BA45, BA47). The cross validation between DSI and fiber dissection revealed a good consistence in the association fiber tracts of Broca’s area. Combining DSI and fiber dissection, this study first identified five association fiber tracts related to Broca’s area and characterized their structure and anatomy comprehensively. The frameworks provided key elements for functional research in Broca’s area.